The Impact of ACFTA on People's Republic of China-ASEAN Trade: Estimates Based on an Extended Gravity Model for Component Trade - Yu Sheng; Hsiao Chink Tang; Xinpeng Xu (Asian Development Bank (ADB), 2012)
This paper uses an extended gravity model to shed light on the impact of the free trade area agreement between the Association of Southeast Asian Nations (ASEAN) and the People's Republic of China (PRC) on the members' trade flows and trade patterns. New determinants that capture the rising importance of global production sharing and intraregional trade in parts and components in East Asia are proposed. Results from the extended gravity model show that the free trade agreement leads to substantially higher bilateral trade between ASEAN and the PRC, more than what a conventional gravity model predicts. The increase is concentrated in the ASEAN countries with stronger industrial linkages with the PRC.
hdl:11540/1302
Keywords: F17; O53; 330; ACFTA; gravity model; parts and components trade; Außenhandel mit Industriegütern; Vorleistungen; Handelsabkommen; Gravitationsmodell; China; ASEAN-Staaten